(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Suitability of cutting technology and cutting parameter is important to produce perfect PCB after cutting process. Defect such as solder mask peel off normally observed during PCB cutting using cutting bit tool. Therefore, it is essential to investigate defect occurrence to obtain suitable cutting parameters such as feed rate and type of cutting bits used to produce good PCB cutting. Different types of PCB cutting bit has been used together with different feed rate to cut the PCB. Quantitative analysis on the defect area has been adopted to represent the degree of defect. The higher normalized value of neatness, the severe the degree of the defect. Quantitative analysis shows bit cutters of WC and WC/TiN with feed rate of 10 mm/s provide minimum thickness of peel off, approximately about 13 µm and 15 µm. Meanwhile WC/TiN bit cutter with feed rate of 10 mm/s shown lowest solder mask peel off approximately 1670 µm². The quantitative value of neatness can be used as a good indicator in accessing the quality of PCB after cutting process.